1986
DOI: 10.1007/bf00219210
|View full text |Cite
|
Sign up to set email alerts
|

Fine structure of the malaria parasite Plasmodium falciparum in human hepatocytes in vitro

Abstract: Recent advances in the ability to culture the hepatic forms of mammalian malaria parasites, particularly of the important human pathogen Plasmodium falciparum have provided novel opportunities to study the ultrastructural organisation of the parasite in its natural host cell the human hepatocyte. In this electron-microscopic and immunofluorescence study we have found the morphology of both parasite and host cell to be well preserved. The exoerythrocytic forms, which may be found at densities of up to 100/cm2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 29 publications
3
10
0
Order By: Relevance
“…Indeed, few of numerous hepatoma cell lines permit the development of the intrahepatic phase of P. falciparum [53,54], and, thus far, none has proved able to sustain satisfactorily the complete development of the parasite. In contrast, human hepatocytes transplanted into treated uPA-SCID mice were sufficiently well differentiated to sustain the development of liver schizonts; their size, reaching 50-60 mm 5 days after inoculation with sporozoites, was as large as that which has been observed in either humans [33] or chimpanzees [6,34] and was twice as large as that which has been observed in primary human-hepatocyte cultures in vitro [55,56]. Furthermore, their development was very homogeneous among the liver schizonts.…”
Section: Discussionmentioning
confidence: 51%
“…Indeed, few of numerous hepatoma cell lines permit the development of the intrahepatic phase of P. falciparum [53,54], and, thus far, none has proved able to sustain satisfactorily the complete development of the parasite. In contrast, human hepatocytes transplanted into treated uPA-SCID mice were sufficiently well differentiated to sustain the development of liver schizonts; their size, reaching 50-60 mm 5 days after inoculation with sporozoites, was as large as that which has been observed in either humans [33] or chimpanzees [6,34] and was twice as large as that which has been observed in primary human-hepatocyte cultures in vitro [55,56]. Furthermore, their development was very homogeneous among the liver schizonts.…”
Section: Discussionmentioning
confidence: 51%
“…The reported sizes of late P. falciparum LSs obtained from in vitro culture range from only 15 to 40 μm in diameter (6,7,39,40), whereas we visualized LS sizes up to 80 μm in diameter, which, based on previous volume calculations (29), contain between 40,000 and 60,000 merozoites. A small number of studies on P. falciparum LS development in humans have been undertaken (41,42), and the size of 6 day LS ranged from 55 to 60 μm.…”
Section: Frg Huhep and Frg Nod Huhep Micementioning
confidence: 45%
“…Of interest is the finding that a peptide form the LSA-1 N-terminal region binds to hepatic cells and to HLA-DRβ1*1101[20], which is consistent with the induction of CD4 + T cell responses in clinical trials[11,21]. Analysis of infected primate liver sections probed with antibodies against LSA-1 has shown that synthesis of LSA-1 begins soon after sporozoite invasion and that the protein accumulates throughout the liver stage development [22,23]. From three days post infection, LSA-1 is detectable in the parasitophorous vacuole (PV), which is delineated by the inner plasmalemma and the outer parasitophorous vacuole membrane (PVM) of the infected hepatocyte, and surrounds the developing merozoites as part of a "flocculent mass" [23].…”
Section: Introductionmentioning
confidence: 71%